1996
DOI: 10.1680/adcr.1996.8.32.167
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the phase composition in OPC and blended cement mortars due to carbonation

Abstract: The effect of carbonation on the phase compositIOn in salt-contaminated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In this sense, many authors have pointed out that alkali in cement favours its carbonation [31][32][33]. Goñi et al [15] studied the influence of the alkalis of cement of two OPC: 1.03% and 0.43% Na 2 O equivalent, on the kinetics of carbonation and concluded that in the case of accelerated carbonation the content of alkalis does not influence the kinetics of the process.…”
Section: Carbonation Thicknessmentioning
confidence: 99%
“…In this sense, many authors have pointed out that alkali in cement favours its carbonation [31][32][33]. Goñi et al [15] studied the influence of the alkalis of cement of two OPC: 1.03% and 0.43% Na 2 O equivalent, on the kinetics of carbonation and concluded that in the case of accelerated carbonation the content of alkalis does not influence the kinetics of the process.…”
Section: Carbonation Thicknessmentioning
confidence: 99%
“…For instance, the amount of calcium carbonate formed due to carbonation depends on the type of cement used and the water content of the concrete 7,8 . Sophisticated testing techniques, such as X-ray diffraction and thermo-gravimetric analysis, could be used to determine the profile of neutralisation of cement hydrates due to carbonation 9,10 . However, these involve the removal of concrete dust from different depths from the exposure surface and the analysis of the dust in a lab.…”
Section: 2mentioning
confidence: 99%